Early Paleozoic Extension-Compression Transition and Formation of a Paleo-Oil Reservoir System in the NW Sichuan Basin: Implications for Deeply Buried Hydrocarbon Accumulation. (27th May 2021) - Liang, Xiao; Liu, Shu-gen; Wu, Liang-liang; Deng, Bin; Li, Jing; Zhang, Meng-lin; Tan, Xu-hang
Abstract : Owing to multiple tectonic events after the Late Triassic, the northern segment of the western Sichuan depression (NSWSCD) has a complex geological history of significant uplift and deeply buried. With abundant oil and gas play in the NSWSCD, the study of paleo-oil reservoir systems and early hydrocarbon accumulation in this area is of great significance for deep marine hydrocarbon distribution prediction in complex structural settings. Analysis on the northern section of the Mianyang-Changning Intracratonic Sag (MY-CN IS) and the Tianjingshan Paleouplift (TJS PU), the two Early Paleozoic tectonic units are laterally superimposed. Combined the reservoir bitumen of the Sinian Dengying Fm firstly, the biomarker (TT23 /tT24, S21 /S22, etc.) and Organic δ 13 C (lighter than 30‰) characteristics indicate that the Sinian-Jurassic paleo-oil system in the TJS PU area is the main source of Lower Cambrian organic-rich black shale. This is closely related to the superimposition and combination effects of the intracratonic sag and paleouplift. Therefore, this study establishes a geological-geochemical accumulation model through a combination of R o and fluid inclusion data. The No. 1 fault is an important zoning fault in the NSWSCD, which significantly controls the division of the oil-gas zone. The process of paleo-oil reservoir destroyed directly only exists in the frontal deformation zone. The deep marine strata of the eastern No. 1 fault demonstrate the four-center hydrocarbon accumulation processes, which include oil generation, gas generation, gas storage, and gas preservation. The superdeep Dengying Fm has long-term exploration potential in the NSWSCD.